Estudos dos fatores que afetam a qualidade microbiológica do frango abatido e comercializado em Fortaleza(CE) - Machado, Nadia Accioly Nogueira (1985)
This study aimed at examining the various factors that affect the microbiological quality of poultry slaughted and marketed in the city of Fortaleza, Brazil. To achieve this objective a random sample of three stablishments were selected: a local manufecturer of chicken food, a poultry processing plant oparating with the continuous slaughter and chilling of poultry methods, and a slaughter house that uses conventional methods of slaughter for immediate consumption. [...]